Sustainable Livelihoods through Community Empowerment in Bumiaji, Batu City, East Java - Setiyo Yuli Handono; Yeni Puspita (Institut Teknologi Sepuluh Nopember, 2019)
The study objective is to analyze sustainable livelihoods (farmers conditions ; social, economic, and income) through community empowerment in the Sumber Brantas Village, Bumiaji, Batu City, East Java Province. The community empowerment program is a program to change plant commodities from garlic plants to potato plants. The research method is qualitative research. The key informants this study include the chairperson and members of Farmer Group